Variance Estimates in Models with the Box-Cox Transformation: Implications for Estimation and Hypothesis Testing - Spitzer, John J. (The Review of Economics and Statistics, 1984)
John J. Spitzer, Variance Estimates in Models with the Box-Cox Transformation: Implications for Estimation and Hypothesis Testing, The Review of Economics and Statistics, Vol. 66, No. 4 (Nov., 1984), pp. 645-652